Parental experiences of prenatal education when preparing for labor and birth of infant with a lethal diagnosis - Urszula Tataj‐Puzyna; Barbara Baranowska; Beata Szlendak; Magdalena Szabat; Maria Węgrzynowska (Wiley, 2023)
Abstract Aim The aim of this study was to describe the unique experiences of parents facing a Life Limiting Fetal Conditions (LLFC) diagnosis, who chose to continue with their pregnancy, as they prepare for childbirth through individual and group prenatal education. Design A qualitative study. Methods We employed the phenomenological approach and the Colaizzi strategy to analyse semi‐structured interviews. Thirteen persons were interviewed. The participants were couples (n = 6) and women (n = 7) who received LLFC and were preparing for birth. Results We described three main paths of prenatal education chosen by parents with LLFC: 'Searching for normality' concerned people participating in conventional prenatal classes (AC) who tried to avoid confronting the situation they faced; 'Searching for communitas' concerned the participation in special AC selected for the opportunity of sharing experiences; 'Searching for an individual way' concerned people who resorted to individual preparation for childbirth, often as a result of delayed planning. Parents should have a choice of various paths of birth preparation, that best meet their preferences.